Prevalence of Feline Coronavirus Antibodies in Japanese Domestic Cats during the Past Decade - TAHARAGUCHI, Satoshi; SOMA, Takehisa; HARA, Motonobu (Journal of Veterinary Medical Science, 2012)
From 2001 to 2010, 17,392 Japanese cats were examined for feline coronavirus (FCoV) antibodies. The seroprevalence of purebreds (66.7%) was higher than that of random breds (31.2%). Seroprevalence increased greatly in purebreds by three months of age, while it did not fluctuate greatly in random breds with aging, indicating that cattery environments can contribute to FCoV epidemics. Purebreds from northern regions of Japan were likely to be seropositive (76.6% in Hokkaido, 80.0% in Tohoku), indicating cattery cats in cold climates might be more closely confined. Among purebreds, the American shorthair, Himalayan, Oriental, Persian, and Siamese showed low seroprevalence, while the American curl, Maine coon, Norwegian forest cat, ragdoll and Scottish fold showed high seroprevalence. There would also be breed-related differences in Japan similar to the previous studies in Australia.